Therapeutic Effect of Carnitine on Atorvastatin induced Mechanical Myotoxicity of Gastrocnemius Muscles of Rats (Medical Forum Monthly, 2024)
Objective: To Study Therapeutic Effect of Carnitine on Atorvastatin-induced Mechanical Myotoxicity of Gastrocnemius Muscles of Rats.Study Design: Observational studyPlace and Duration of Study: This study was conducted at Department of Physiology, University of Karachi, from 21st January 2012 to 30th December 2013.Materials and Methods: Present study showed that effect of statin on mechanical properties of gastrocnemius muscle of rats and use of carnitine as prevention of statin induced myopathies. Animals were injected statin for 6 weeks in one group and carnitine to another group along with statin to study the possible therapeutic effect. After treatment period, animals were decapitated and gastrocnemius muscles were isolated. Twitch and tetanus of muscles were recorded in each group.Results: Our results showed that treatment of statin reduced the body weight of animals and increased the resting length (106%) of isolated gastrocnemius muscles. We also observed that force of contraction of both twitch and tetanus in statin treated group were significantly reduced (P>0.0001). This negative effect of statin on twitch and tetanus parameters of muscle was partially decreased by an additive treatment of carnitine.Conclusion: Thus, carnitine plays a vital role in improving muscle contractile ability caused by statins. Our study demonstrated the potential preventive measure of atorvastatin-induced myopathy using carnitine and its impacts on mechanical function of muscles.